K.H Ahmad Dahlan's Concept of Thought in the World of Education in the 21st Century - Erwin Erwin; Dedi Kuswandi (Edumaspul: Jurnal Pendidikan, 2024)
The aim of this research is to describe the concept of K.A Ahmad Dahlan’s educational thought in the world of 21 st century educational to be used as a learning models in the current era. This research uses the library research method, date is collected based on information obtained from source books, research articles and other information via the internet. Data analysis was carried out using deductive and inductive approaches. From the results of the collection of information obtained, there is a close connection to the 21st century, namely concepts such as the five characteristics of a Progressive Islamic Treatise, adaptation of the bayani-burhani-irfani epistemology, responsiveness to developments in information technology, diversification of Muhammadiyah schools, best future practices, and internationalization of Muhammadiyah education. the main foundation in efforts to renew education in the 2nd century of Muhammadiyah. With proper contextualization and application of these concepts, Muhammadiyah can continue to develop as an educational force that plays a role in forming a generation that is qualified, competitive and committed to Islamic values amidst the dynamics of modern civilization.